2004
DOI: 10.1001/archinte.164.6.645
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Health Maintenance Organization Coverage of Self-monitoring Devices on Diabetes Self-care and Glycemic Control

Abstract: Providing free glucose monitors improved rates of self-monitoring in this health maintenance organization population, possibly by offering an initial incentive for patients to engage in more desirable patterns of care. Initiating SMBG was associated with increased regularity of medication use and a reduction in high blood glucose levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 33 publications
5
54
0
1
Order By: Relevance
“…In these patients, an SMBG frequency of at least once per day was related to significantly higher levels of distress and worries. In other studies, increased use of SMBG has been shown to be associated with improved medication compliance [8,26]. We found that patients in the SMBG group visited the treating physician more frequently.…”
Section: Hr (95% Ci)supporting
confidence: 54%
“…In these patients, an SMBG frequency of at least once per day was related to significantly higher levels of distress and worries. In other studies, increased use of SMBG has been shown to be associated with improved medication compliance [8,26]. We found that patients in the SMBG group visited the treating physician more frequently.…”
Section: Hr (95% Ci)supporting
confidence: 54%
“…Similar findings were reported in other community-based studies [134,135]. In contrast, other studies found glycaemic deterioration with increased monitoring frequency among poorly controlled individuals with type 2 diabetes on insulin treatment [126,129].…”
Section: Factors To Effectiveness Of Smbgsupporting
confidence: 89%
“…Family support and self-efficacy were noted to increase testing frequency [124,125,135,141,142]. Cost is another significant predictor of less frequent monitoring [124,125,135,141,142]. Although Harris in 2001 found no association between socio-economic status and SMBG frequency, 90% of his subjects had health insurance [126].…”
Section: Confounders To Adherence To Smbgmentioning
confidence: 99%
See 1 more Smart Citation
“…This reduced test strip use from 9.5 to 4.7 per week without significant change in glycemic control. In a second study (42), the intervention was provision of free blood glucose meters, which increased average SMBG in sulfonylureatreated patients from 0.5 to 2.0 tests per week without a significant A1C reduction in all but the worst-controlled patients. By contrast, in the only valid randomized controlled trial with sufficient power to detect a significant SMBG effect in OHAtreated patients (14), the required testing frequency was six times per week, which was associated with a reduction in A1C of 0.28%.…”
Section: Longitudinal Cohortmentioning
confidence: 99%